The Difference of Reading Comprehension Between the Students Who Are Taught by Using KWL Strategy and Students Who Are Not in The Year Ten Students of SMA Negeri 1 Mamasa - Rehatalanit, Ivana Chrysalia; Korompot, Chairil Anwar; Sakkir, Geminastiti (Celebes Journal of Language Studies, 2024)
The aim of this research is to find out the effects of the KWL method on reading comprehension skills, specifically to determine if there is a difference in reading comprehension between students taught using the KWL Strategy and those who are not. This study was conducted at SMA Negeri 1 Mamasa over the course of one month (4 meetings), with two groups: an experimental group and a control group, totaling 72 participants (36 in each group). The treatment was applied to the Experimental group, while the Control group did not receive it. The study used SPSS to analyze the data to determine the differences in scores between the experimental and control groups. The result of the Independent Samples t-test shows a significance (2-tailed) value < 0.05, specifically 0.000, indicating a significant difference between the Experimental group and the Control group. This outcome signifies that the use of the Know, Want, and Learn method has led to a statistically significant improvement in students' reading comprehension at SMA Negeri 1 Mamasa.